Ontogenic expression of human carboxylesterase-2 and cytochrome P450 3A4 in liver and duodenum: Postnatal surge and organ-dependent regulation. (1st April 2015) - Chen, Yi-Tzai; Trzoss, Lynnie; Yang, Dongfang; Yan, Bingfang
Abstract: Human carboxylesterase-2 (CES2) and cytochrome P450 3A4 (CYP3A4) are two major drug metabolizing enzymes that play critical roles in hydrolytic and oxidative biotransformation, respectively. They share substrates but may have opposite effect on therapeutic potential such as the metabolism of the anticancer prodrug irinotecan. Both CES2 and CYP3A4 are expressed in the liver and the gastrointestinal tract. This study was conducted to determine whether CES2 and CYP3A4 are expressed under developmental regulation and whether the regulation occurs differentially between the liver and duodenum. A large number of tissues (112) were collected with majority of them from donors at 1–198 days of age. In addition, multi-sampling (liver, duodenum and jejunum) was performed in some donors. The expression was determined at mRNA and protein levels. In the liver, CES2 and CYP3A4 mRNA exhibited a postnatal surge (1 versus 2 months of age) by 2.7 and 29 fold, respectively. CYP3A4 but not CES2 mRNA in certain pediatric groups reached or even exceeded the adult level. The duodenal samples, on the other hand, showed a gene-specific expression pattern at mRNA level. CES2 mRNA increased with age but the opposite was true with CYP3A4 mRNA. The levels of CES2 and CYP3A4 protein, on the other hand, increased with age in both liver and duodenum. The multi-sampling study demonstrated significant correlation of CES2 expression between the duodenum and jejunum. However, neither duodenal nor jejunal expression correlated with hepatic expression of CES2. These findings establish that developmental regulation occurs in a gene and organ-dependent manner.